The Importance of Artificial Intelligence Systems in Providing Information Security - Mamasoliev Bakhodir Akhmadalievich (Genius Journals, 2023)
This article analyzes the importance of artificial intelligence systems in ensuring information security, and considers the main principles and importance of ensuring information security
Keywords: information security; artificial intelligence; cyber threat